METODE BERTIPE STEFFENSEN DENGAN ORDE KONVERGENSI OPTIMAL UNTUK MENYELESAIKAN PERSAMAAN NONLINEAR - Sarbaini '; Imran M.; Asmara Karma (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses a mo dification of a third order Steffensen-typ e method, by adding three different weight functions into the third order Steffensen-type method, so that we obtain three different correction Steffensen-typ e metho ds. These methods are of order three and require three function evaluations p er iteration so that their index of efficiency is 1.587. Computational results show the correction Steffensentype methods are competitive enough in their class.